Model Pengembangan Pariwisata Berkelanjutan Berbasis Toponimi di Danau Perintis Kabupaten Bone Bolango - Susanna Deswita Lase; Sunarty Suly Eraku; Moch. Rio Pambudi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Toponymy reflects the historical, cultural, and geographical identity of a place and can serve as an important foundation for sustainable tourism development. However, the potential of toponymy has not been widely integrated into tourism planning, particularly in local tourist destinations with strong historical values such as Perintis Lake. This study aims to formulate a toponymy-based sustainable tourism development model at Perintis Lake, Bone Bolango Regency. The study was conducted through an analysis of the toponymy of Perintis Lake based on physical and social geographic aspects and its potential to support sustainable tourism development. The study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the name of Perintis Lake is related to the historical event of the arrival of Hasanuddin Division troops using KM Perintis in 1957 in order to maintain the integrity of the Unitary State of the Republic of Indonesia. The toponymy contains historical value, local identity, and collective memory of the community that is still maintained to this day. From a physical geographic aspect, Perintis Lake has a water landscape that supports tourism activities and the ecological function of the area. From a social geographic aspect, this area becomes a space for community activities and has cultural and historical values that have the potential to be developed as a tourism narrative. Based on the analysis results, the toponymy-based sustainable tourism development model at Perintis Lake consists of strengthening destination identity, tourism interpretation based on local history, environmental preservation, community empowerment, and culture-based promotion. This model supports sustainable tourism development through the integration of environmental, socio-cultural, and economic aspects while strengthening the local identity of the Perintis Lake tourist destination.